Islamic Human Resource Management dalam Society 5.0 sebagai Strategi Pengembangan SDM Islami di Era Digital - Rabiatul Munawarah; Khuzaini; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
The development of the Society 5.0 era has brought fundamental changes to the paradigm of human resource management. This concept places humans at the center of innovation and technology, demanding a balance between digital advancement and human values. This study aims to examine the integration of the International Human Resource Management (IHRM) concept with Society 5.0 as a strategy for developing Islamic human resources in the digital era. The research method used is qualitative with a literature study approach, reviewing various relevant previous studies. The findings indicate that the application of IHRM principles in a technology-based work environment can strengthen employees’ spiritual well-being, enhance loyalty, and promote the creation of sustainable organizations